"They are notoriously not very honest": provider-based stigma and the challenge of integrated care for women experiencing IPV and OUD - McLean, Katherine (Journal of family violence, 2026)
Purpose: A growing literature has documented the frequent co-occurrence of opioid use disorder (OUD) and intimate partner violence (IPV) among women, with IPV victimization prevalence among women with OUD estimated between 44 and 90%. Prior research has identified significant barriers to care for women dealing with IPV or OUD in isolation - barriers that may be further amplified by co-morbidity. Methods: Recruiting a diverse cross-section of professionals (n = 39) who serve women with co-occurring IPV/OUD, this project used semi-structured interviews to describe the unique impediments to engaging and retaining this population within relevant programming, including health care, housing, IPV, and substance use services. Results: Stigma against both women experiencing IPV and people who use opioids (PWUO) was cited as a major barrier by participants, who described the ways in which stigma deterred service-seeking, service enrollment, and long-term retention. At the same time, many providers expressed stigmatizing attitudes toward women with co-occurring IPV/OUD, characterizing them as blameworthy, dangerous, and incapable of, or unwilling to, change. Conclusion: Provider-based stigma is prevalent, yet maybe be largely unacknowledged, among professionals who serve women with co-occurring IPV/OUD. Medical-legal partnerships that integrate care for this population, putting OUD and IPV providers in direct collaboration, may mitigate provider-based stigma.